Prevalence and pattern of self-medication among COVID-19 infected students of Birat Medical College Teaching Hospital: - Yadav, Binita; Yadav, Arbind Kumar; Rai, Prakash (Birat Journal of Health Sciences, 2025)
Introduction: Self-medication is a common practice in Nepal. It provides a ready low-cost alternative for people in low and middle-income country like Nepal. During the pandemic, the growing influence of social media, accessibility of over-the-counter medications, and fear of contracting the virus may have led to self-medication practices among the public. Medical students are prone to such practices due to relevant background knowledge, and access to drugs. This study was carried out to determine the prevalence, pattern, sources, and impact of self-medication practice among medical students of Birat Medical College-Teaching Hospital.Methodology: A cross-sectional study was conducted online among 200 students of Birat Medical College-Teaching Hospital, Nepal from April to May 2021, to explore the prevalence, pattern and source of self-medication practices and the reasons to use. Ethical approval was obtained from institutional review committee of BMCTH, and verbal consent was taken from each participant before data collection. Descriptive statistics as frequency, percentage and graphs were used to analyze the collected information.Results: Though 200 participants were enrolled in the study, only 155 (77.5%) completely filled the form and submitted. Majority of the respondents 84(54.2%) were males and higher numbers were in 18–24 years age group. Out of 155 respondents, 102 (65.8%) were infected with COVID-19. The prevalence of self-medication was 30.2% in this study. Self-medication practice did not differ significantly between male and female students. The most commonly used medications were Paracetamol 29 (18.7%), Azithromycin 13(8.4%), Ibuprofen 12(7.7%), and Vitamin C 11 (7.0%). The most frequently reported ailments were fever 33 (21.3%), body ache 26(16.8%) and sore throat 20 (12.9%). About 60 respondents (38.7%) took medications when they developed symptoms of COVID-19.  Pharmacies 30(19.3%) were the main source of drugs. Paracetamol was the most commonly used drug for self-medication.Conclusion: This study identified that the main drugs used during COVID-19 outbreak was Paracetamol 29 (18.7%) and Azithromycin 13(8.4%). If not used carefully, self-medication can lead to risks of developing antibiotic resistance, adverse drug reactions and financial loss. Efforts should be done to educate the advantages and disadvantages of self-medication along with its proper use.